JAMUR ARBUSKULA DI TAMAN NASIONAL UJUNG KULON - Kartini Kramadibrata (Research Center for Biology-Indonesian Institute of Sciences, 2012)
Study on diversity of arbuscular fungi (AF) of several rizosphere of forest trees and shrub in Karang Ranjang Post, Karang Ranjang Resort,Ujung Kulon National Park (TNUK) was done. Ninety-six soil samples from 23 forest trees were collected for examining AF. Each soil sample was placed into a plastic bag and record the host plant then air dried. Part of the samples were wet sieved by using four type of soil sieves, another part were kept as pot culture in the green house for about six to twelve months, then wet sieved. There were three species of Acaulospora, six species of Glomus, one species of Sclerocytis and one species of Paraglomus associated with forest trees and shrub in TNUK. Most of species recorded from this area are common, except Glomus multicaulis.